2019
DOI: 10.1093/jas/skz067
|View full text |Cite
|
Sign up to set email alerts
|

Effects of long-term diet supplementation with Gliricidia sepium foliage mixed with Enterolobium cyclocarpum pods on enteric methane, apparent digestibility, and rumen microbial population in crossbred heifers

Abstract: Effects of long-term diet supplementation with Gliricidia sepium foliage mixed with Enterolobium cyclocarpum pods on enteric methane, apparent digestibility, and rumen microbial population in crossbred heifers The International Center for Tropical Agriculture (CIAT) believes that open access contributes to its mission of reducing hunger and poverty, and improving human nutrition in the tropics through research aimed at increasing the eco-efficiency of agriculture. CIAT is committed to creating and sharing know… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 55 publications
0
6
0
1
Order By: Relevance
“…For example, (67) reported Y m values ranging between 6.7% and 11.4% in mature Brahman cattle fed with diets based on tropical forages and ( 17) reported Y m values of 7.96 in cattle consuming a 74% Cynodon plectostachyus and 26% L. leucocephala diet, and of 9.42 when receiving a 100% C. plectostachyus diet. Also, Molina-Botero et al (79) reported that heifers supplemented with Gliricidia sepium foliage mixed with ground pods of Enterolobium cyclocarpum presented less GE loss in the form of CH 4 (Y m = 7.59%) than those fed with grassalone (Y m above 8.1%). In those reports and the present study, it seems improving the quality of the diets offered, resulted in more efficient use of consumed energy, which results in lower Y m values.…”
Section: Methane Emissionsmentioning
confidence: 99%
“…For example, (67) reported Y m values ranging between 6.7% and 11.4% in mature Brahman cattle fed with diets based on tropical forages and ( 17) reported Y m values of 7.96 in cattle consuming a 74% Cynodon plectostachyus and 26% L. leucocephala diet, and of 9.42 when receiving a 100% C. plectostachyus diet. Also, Molina-Botero et al (79) reported that heifers supplemented with Gliricidia sepium foliage mixed with ground pods of Enterolobium cyclocarpum presented less GE loss in the form of CH 4 (Y m = 7.59%) than those fed with grassalone (Y m above 8.1%). In those reports and the present study, it seems improving the quality of the diets offered, resulted in more efficient use of consumed energy, which results in lower Y m values.…”
Section: Methane Emissionsmentioning
confidence: 99%
“…Previous studies have reported lower methane emissions when tropical legume shrubs or trees are incorporated in cattle diets due to the presence of secondary metabolites, such as condensed tannins and saponins [31,32,[99][100][101][102][103]. Despite the relatively low intake of L. leucocephala in this study, the decrease in methane emissions may be a result of the inclusion of this legume in the diet [7,32,100].…”
Section: Methane Emissionsmentioning
confidence: 50%
“…In addition, the estimate of CH 4 was not affected by supplementation in this study under investigation. Molina-Botero et al [ 31 ] found that putting dairy cows in respiration chambers with rutin (glucrohamnoside of quercetin) did not change how they used energy or reduced CH 4 . A wide variety of outcomes may be achieved by the utilization of secondary compounds for the reduction of CH 4 production.…”
Section: Discussionmentioning
confidence: 99%